2022
DOI: 10.1101/2022.12.06.519350
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fetal cannabidiol (CBD) exposure alters thermal pain sensitivity, cognition, and prefrontal cortex excitability

Abstract: Thousands of people suffer from nausea with pregnancy each year. Nausea can be alleviated with cannabidiol (CBD), a primary component of cannabis that is widely available. However, is it unknown how fetal CBD exposure affects embryonic development and postnatal outcomes. CBD binds and activates receptors that are important for fetal development and are expressed in the fetal brain, including serotonin receptors (5HT1A), voltage-gated potassium (Kv)7 receptors, and the transient potential vanilloid 1 receptor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…Because there are few studies that have determined the safety or efficacy of CBD during gestation or lactation (Wanner et al, 2021;Iezzi et al, 2022;Maciel et al, 2022;Swenson et al, 2023), our study monitored maternal health of the dams, early-life health metrics of the offspring, as well as persistent metabolic health of the offspring as adults. We discovered that oral consumption of CBD by pregnant dams did not significantly affect maternal weight gain, duration of gestation, or size of the litter, however, survival to weaning age was significantly reduced in gestationally-exposed pups that were not cross-fostered at birth to drug-free dams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because there are few studies that have determined the safety or efficacy of CBD during gestation or lactation (Wanner et al, 2021;Iezzi et al, 2022;Maciel et al, 2022;Swenson et al, 2023), our study monitored maternal health of the dams, early-life health metrics of the offspring, as well as persistent metabolic health of the offspring as adults. We discovered that oral consumption of CBD by pregnant dams did not significantly affect maternal weight gain, duration of gestation, or size of the litter, however, survival to weaning age was significantly reduced in gestationally-exposed pups that were not cross-fostered at birth to drug-free dams.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is known that cannabinoids cross the placenta as well as the blood-brain barrier, and have been detected in breast milk (Perez-Reyes et al 1982;Bar-Oz et al 2003;Shou et al 2009;Ochiai et al, 2021), few preclinical studies have been performed (Wanner et al, 2021;Iezzi et al, 2022;Maciel et al, 2022;Swenson et al, 2023) that could advise safety precautions in the use of CBD during pregnancy. Studies have shown detrimental effects of prenatal Cannabis use -including early and long-lasting effects on cognitive function, placental abnormalities, fetal growth restrictions, and low birth weight and preterm delivery (Gunn et al, 2016;Natale et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although the cannabis oil used was low in cannabidiol (CBD) (<1 mg/mL), we were interested in CBD levels in the dams and pups, as it acts as negative allosteric modulator of CB1R (Laprairie et al, 2015), and has its own effects of neurodevelopment (Black et al, 2023;Iezzi et al, 2022;Swenson et al, 2023). CBD plasma concentrations showed a similar pattern (Figure 1c), with no significant effect of time (one-way ANOVA, F (4,20) = 1.72, p = .19).…”
Section: Maternal Plasmamentioning
confidence: 99%
“…This method of measuring Cannabis consumption in humans makes comparing cannabinoid doses and exposures between clinical assessments and pre-clinical smoke exposure models challenging. Whereas prior preclinical studies have explored injection, inhalation, and oral administration of isolated THC or CBD [34][35][36][37]55,56,[62][63][64][65], administering THC and/or CBD alone fails to take into consideration the potential effects of other phytocannabinoids, terpenes, and flavonoids of the Cannabis plant as well as the smoke of a combusted product [10,66,67]. Our group has previously worked to establish rat models of Cannabis smoke exposure in the contexts of absence epilepsy [82], cognition [68], and prenatal exposure during pregnancy on offspring health and behaviour [57].…”
Section: Introductionmentioning
confidence: 99%